Corporate social responsibility programmes and their impact on business decision making - Knox, Simon; Maklan, Stan (Cranfield University, 2005)
Based upon an empirical study of CSR programmes across a number of multinational companies, we explore some of the underlying reasons why CSR seems to have a low impact on business decision-making through a validated framework linking CSR programmes with business and social outcomes.